IMPLEMENTASI PEMBELAJARAN NILAI AGAMA DAN MORAL MELALUI METODE PEMBIASAAN DI PAUD AL-BARKAH - Kurniasih, Neng; Mayasari, Mayasari; Nurhaedah, Nurhaedah; Hidayat, Yusuf (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
One of the efforts to result qualified generation is to instill religious and moral values to early childhood since early age. This study aims to find out how to implement learning religious and moral values through the habituation method in PAUD Al-Barkah, and what strategies are used by teachers to implement learning religious and moral values through the habituation method at PAUD Al-Barkah. The method used in this study is a classroom action research (CAR). The results of this study show that the implementation of learning religious and moral values through habituation method to early childhood is categorized very good. This is referring to the increase on the average score in the pre-cycle by 56.5% to 69.8% in the cycle I, and the average score increased to 84.8% in the cycle 2. In addition, the implementation of learning religious and moral values through habituation method has a positive impact on the entire early chidlhoods on the indicators: doing worship, behaving honestly and politely, maintaining personal and environmental cleanliness, and knowing religious days. To conclude that the use of habituation method has positive and significant impact on applying religious and moral values to early childhood at PAUD Al-Barkah.